Design of the low-loss waveguide coil for interferometric integrated optic gyroscopes *Project supported by the National Natural Science Foundation of China (Nos. 61274066, 61504138, 61474115) and the National Key Research and Development Program of China (No. 2016YFA02005003). (April 2017) - Fei, Yao; Yang, Tianshu; Li, Zhaofeng; Liu, Wen; Wang, Xiaodong; Zheng, Wanhua; Yang, Fuhua
Abstract: With the development of manufacturing technology, the propagation loss of the planar waveguide is getting lower and lower, and the shot-noise-limited sensitivity of an IIOG will be greatly improved. When the propagation loss is getting lower, improper coupling-out waveguide in the waveguide coil may lead to non-ignorable bending loss and crosstalk because of the small radius of curvature and X-junction. In this paper, different coupling-out waveguides have been designed. After calculation and optimization by the beam propagation method, we found the proper coupling-out waveguide having relatively low propagation loss, which can improve the sensitivity of the IIOG.